Risk profiling for cirrhosis and hepatocellular carcinoma in HFE hemochromatosis using mobilizable iron stores and alcohol consumption - Mitchell, Natasha D. P.; Pierre, Timothy G. St; Ramm, Louise E.; Ramm, Grant A.; Olynyk, John K. (Scientific reports, 2025)
HFE hemochromatosis (HH) may cause cirrhosis and hepatocellular carcinoma (HCC). Progression to these endpoints depends on the severity of iron overload and cofactors, such as alcohol. We evaluated alcohol and iron-related risk factors in relation to cirrhosis at diagnosis and future development of HCC in a retrospective analysis of 197 HH subjects. The proportion of subjects either with cirrhosis or who developed HCC during follow-up were 29/197 (14.7%) or 10/197 (5.1%), respectively. The median (IQR) follow-up time after diagnosis was 15.2 (4.6 to 22.1) years. The median mobilizable iron stores and daily alcohol consumption (IQR) were 6.0 (3.8–11.0) g and 20 (0–40) g, respectively. An optimal logistic regression model for the odds of cirrhosis was developed by adding candidate liver insult variables (mobilizable iron, alcohol consumption, and age as a surrogate for duration of exposure) in a forward stepwise strategy using area under the receiver operating characteristic curve (AUROC) analysis and the corrected Akaike information criterion. This model demonstrated an AUROC (95% CI) of 0.966 (0.935–0.996), with sensitivity 76 (58–88)% and specificity 97 (93–99) % for prediction of cirrhosis and had a negative predictive value of 99.4 (95% CI 96.7–99.97) % for development of HCC. Thus, future risk of HCC can be assessed from mobilizable iron stores and alcohol consumption of HH subjects.